تأثير نظام الحوافز على رضا العاملين في المؤسسات العمومية الجزائرية "دراسة اتجاهات عينة من موظفي تعاونية الحبوب والخضر الجافة بالبويرة" - أولاد حيمودة, عبد اللطيف; بن مير, محمد الطيب; طويطي, مصطفى (University of Eloued جامعة الوادي, 2017)
هدفت الدراسة إلى التعرف على مدى تأثير نظام الحوافز على رضا العاملين في مؤسسة تعاونية الحبوب والخضر الجافة بالبويرة، ولتحقيق الأهداف المرجوة من هذه الدراسة، فقد تم تصميم استبيان تضمن تقدير للمتغيرات الأساسية (الحوافز المادية، الحوافز المعنوية والرضا الوظيفي). ثم وزعت على عينة اختيرت بشكل عشوائي من بين مجموع موظفي هذه المؤسسة، والتي بلغ عددها 120 موظف. توصلت الدراسة لنتائج هامة، تمثلت في أن لدى العاملين بالمؤسسة اتجاه إيجابي نحو الحوافز المادية مقارنة بالحوافز المعنوية، كما أن هناك شبه اتفاق لدى العاملين بأن نظام الحوافز في المؤسسة مقبول نوعا ما، حيث تجاوز قيمة المتوسط الحسابي القيمة المعيارية، أما بالنسبة لمستوى رضا العاملين داخل المؤسسة، فهو الآخر كانت نتيجته إيجابية حيث بلغت قيمة المتوسط الحسابي 3,123 ، مما يعني أن الوزن النسبي لرضا العاملين في تعاونية الحبوب والخضر الجافة بولاية البويرة تجاوزت 62,46% . Abstract: This study aimed at identifying the effect of the incentive system on the satisfaction of employees in the cooperative of grain and dry vegetables in Bouira,in order To achieve the objectives of this study, a questionnaire was designed to estimate the basic variables (Material incentives, moral incentives and job satisfaction),And then distributed to a random sample of the employees of this institution, which numbered 120 employees. The study concluded with significant results, which is the positive trend of workers towards physical incentives compared to moral incentives, There is also consensus among employees that the incentive system in the institution is somewhat acceptable, Where the value of the arithmetic mean exceeded the standard value, As for the level of satisfaction of employees within the institution, it was a positive result with an average value of 3,123, which means that the relative weight of the satisfaction of employees in the cooperative grain and dry vegetables in the state of Bouira exceeded 62.46%
The impact of the incentive system on the satisfaction of workers in Algerian public institutions "Study of the trends of a sample of employees of the cooperative of grain and dry vegetables in Bouira"
مجلة رؤى المجلد السابع العدد 12
Keywords: الحوافز المادية، الحوافز المعنوية، نظام الحوافز، رضا العاملين; material incentives, moral incentives, incentive system, employees satisfaction. (JEL) Classification : M120,C210,C250.